NYI BEI MARDUSARI DALAM LANGENDRIYAN MANGKUNEGARAN: SEBUAH TINJAUAN MENGENAI KUALITAS KEPENARIAN SILANG KARAKTER - Darmasti - (Pascasarjana Institut Seni Indonesia Surakarta, 2010)
This biography of Nyi Tumenggung Mardusari aims to discover her role as an all round artist within the environment of the Mangkunegaran. It is important to do so as her works and ability as an artist have made her a role model for subsequent generations. Her life spanned numerous events and a variety of situations of the era. A multidimensional approach was used, with concepts borrowed from the social sciences, beginning with Mardusari’s background from childhood until she entered the Mangkunegaran, covering her various cultural influences from the palace, methods of study, work experience, creative experience, and the award she received. Her success as an artist was closely connected with her hard work in developing her talent, and the encouragement and opportunities given to her by Mangkunegara VII, who gave her guidance. Other direction was provided by her art teacher, who helped mould her into a revered artist. Nyi Tumenggung Mardusari’s presence as an artist showed her artistic ability in numerous fields, in each of which she excelled: as a dancer, a pesindhen, a batik worker, and a makeup specialist for Surakarta style wedding. Her ability was recognized by many people, both inside and outside the palace and even abroad. As we know, langendriyan have become a very famous show in Mangkunegaran palace. Mardusari’s dance role as Menak Jingga become an example of a crossed gender phenomenon on dance tradition. Its role have comprehended conditions which must be done by and to be a good dancer.Keywords: biography, langendriyan, crossed-gender role